Ischaemia alters the effects of cardiomyocyte-derived extracellular vesicles on macrophage activation - Almeida Paiva, Rafael (2018)
We thank Dr Nuno Alves (Cardiology Department, CHUC‐HG) who performed the collection of human blood samples and Doctor Francisco Caramelo (iCBR/FMUC) for helping with the statistical analysis. This work was supported by the European Regional Development Fund (ERDF) through the Operational Program for Competitiveness Factors (COMPETE) [under the projects PAC “NETDIAMOND” POCI‐01‐0145‐FEDER‐016385; HealthyAging2020 CENTRO‐01‐0145‐ FEDER‐000012‐N2323; POCI‐01‐0145‐FEDER‐007440, CENTRO‐01‐ 0145‐FEDER‐032179, CENTRO‐01‐0145‐FEDER‐032414 and FCT‐ UID/NEU/04539/2013 to CNC.IBILI]. TMM was supported by PD/ BD/106043/2015 and TRR by PD/BD/52294/2013 from Fundação para a Ciência e a Tecnologia (FCT). JS was supported by Horizon2020 ERC‐2016‐COG EVICARE (725229).